2014
DOI: 10.1088/0004-637x/787/1/13
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Composition of the Sun From Helioseismic and Solar Neutrino Data

Abstract: We perform a quantitative analysis of the solar composition problem by using a statistical approach that allows us to combine the information provided by helioseimic and solar neutrino data in an effective way. We include in our analysis the helioseismic determinations of the surface helium abundance and of the depth of the convective envelope, the measurements of the 7 Be and 8 B neutrino fluxes, the sound speed profile inferred from helioseismic frequencies. We provide all the ingredients to describe how the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
145
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(161 citation statements)
references
References 57 publications
(76 reference statements)
13
145
2
Order By: Relevance
“…This rather high oxygen abundance was supported by the work of Ayres et al (2013), who used a CO5BOLD model atmosphere to analyze molecular CO lines (assuming n(C)/n(O) = 0.5) and derived A(O) = 8.78 ± 0.02 dex. Villante et al (2014) has shown that the chemical composition presented by Caffau et al (2011), which includes a "high" A(O), is in much better agreement with the overall metal abundance inferred from helioseismology and solar neutrino data.…”
Section: Introductionmentioning
confidence: 68%
“…This rather high oxygen abundance was supported by the work of Ayres et al (2013), who used a CO5BOLD model atmosphere to analyze molecular CO lines (assuming n(C)/n(O) = 0.5) and derived A(O) = 8.78 ± 0.02 dex. Villante et al (2014) has shown that the chemical composition presented by Caffau et al (2011), which includes a "high" A(O), is in much better agreement with the overall metal abundance inferred from helioseismology and solar neutrino data.…”
Section: Introductionmentioning
confidence: 68%
“…It is well known that with the current available input physics and the Asplund et al (2009) abundances a 1 M star at the current age of the Solar System does not give a structure consistent with helioseismic measurements (see e.g. Villante et al 2014, and references therein). Specifically, one cannot produce a model that fits the current radius and luminosity of the Sun which also has the correct depth of the convective envelope.…”
Section: The Effects Of the Choice Of Solar Calibrationmentioning
confidence: 97%
“…For solar metallicity we adopt Z ⊙ = 0.02 (Villante et al 2014). This is the result of the fact that stars at high metallicity are subject to intensive stellar wind mass loss (Vink 2011) and they do not form helium cores above 45 M ⊙ (see Fig.…”
Section: Mass Of Single Bhs and Bh-bh Mergersmentioning
confidence: 99%